Performance Testing of Indonesian Hydrocarbon Refrigerants - Tandian, N. P; Suwono, A; Pasek, A. D; Hardianto, T; Soelaiman, T. A; Prasetyo, B. T; Sarwono, Sarwono; Kafiuddin, Kafiuddin (Mesin, 1999)
In conjunction with the CFC phase out, IURC-ES ITB has been concentrating its research of HC refrigerant on âpropane natural butaneâ (PNB) refrigerant. The test results obtained in IURC-ES ITB during the development of the PNB refrigerant showed that PNB has better performance than PIB and CFC-12. The field tests of PNB also showed the similar results. Recently, to reconï¬rm the previous test results, the performance of PNB, PIB and CFC-I2 were compared in a series of performance tests in the LTMP Serpong. The tests also show that PNB consistently has better performance compared to PIB and CFC-12. This paper also reports the current development of PNB refrigerant in IURC-ES ITB.